Instrumental indicators of desirable texture attributes of French fries. (May 2021) - Sadeghi, Rohollah; Lin, Yulian; Price, William J.; Thornton, Michael K.; Hui-Mei Lin, Amy
Abstract: The texture quality of French fries is critical to the potato processing industry. Sensory evaluation via testing mouth sensation or by visual and finger spinning inspection are the primary methods to assess French fry texture quality. Instrumental texture analysis has not been practically used due to data inconsistency. This study aimed to minimize variations of instrumental analysis and identify instrumental parameters with strong correlations to a sensory evaluation to enhance the effectiveness of the texture quality assessment. This research was carried out on an industrial scale and utilized 10 potato varieties to increase the texture variation of samples. The sensory evaluation by the visual and finger spinning inspection was performed following industrial procedures and standards. Results showed instrumental crispness and crunchiness, as represented by the slope of the first significant fracture and the number of fractures of the force-distance curve in a cut test with a T-42 blade, were strongly correlated with desirable sensory attributes. Microstructure examination revealed that a low level of crust compactness was associated with instrumental crispness and crunchiness. The procedure advanced in this study had a small data variation and concluded that instrumental crispness and crunchiness are strong indicators of premium French fry texture quality. Highlights: The instrumental texture analysis correlated well with the visual and finger spinning based sensory evaluation Instrumental crispness and crunchiness are strong indicators of desirable texture attributes A low level of crust compactness is positively associated with desirable texture attributes